Moloch en expansion - Agnès Bouvier (Flaubert: Revue Critique et Génétique)
What Salammbô tells usis about ourselves: as heirs to the Christian tradition but also as human beings, belonging to that human race of which Voltaire claimed that nobody could read its history without abhorrence. The whole of human history is pervaded by “molochism” in Flaubert’s Carthage where all peoples and religions melt, merge and become barbarous in contact with each other. The human race is under the spell of Moloch, everywhere and at all times. First of all, molochism is at work in Greece, and that means “us” in the sense implied by Flaubert when he replied to Sainte-Beuve’s criticism for “not having introduced among the Greeks a philosopher, a man of reason who could have lectured us on morals, or done good deeds, a gentleman, in a word, ‘who feels as we feel’”. The bloody trail of Moloch can be followed throughout Europe, and it leads to another part of ourselves: Gaul. The presence of the Gauls in the background of Moloch’s description is no more a writer’s device than the presence of the Greeks in the procession leading up to the children’s sacrifice in chapter XIII. It is deliberately meant by Flaubert to show “Moloch” in its full significance, as an historical, theological and anthropological phenomenon, a terrifying whole. The accumulation of cultural references raise endless foundations to the statue revived in Salammbô. What was scattered is now put together, what was hidden now comes out: “All the temples at the same time” reopen in order to celebrate the “Supreme Baal”, and even things that have become meaningless to everyone gather round Moloch: « forgotten idols reappeared ». Although forgotten, they are still present.